2003
DOI: 10.1063/1.1578993
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methylchloride on Si(100) from first principles

Abstract: The chemisorption of methylchloride (CH3Cl) on Si(100) is studied from first principles. We find that, among a number of possible adsorption configurations, the lowest-energy structure is one in which the methylchloride molecule is dissociated into CH3 and Cl fragments which are bound to the two Si atoms of the same surface dimer. Our calculations show that dissociative chemisorption of methylchloride on Si(100) may proceed along different reaction paths characterized by different energy barriers that the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 27 publications
6
35
0
Order By: Relevance
“…This can be rationalized by the high sticking probability of 1 at low temperatures below 320 K in Fig. 3 and the relatively small kinetic energy compared to the expected potential well depth of 270 meV for the precursor state [27]. At a higher energy of E i 180 meV, an incoming molecule collides with a more corrugated repulsive wall of the potential, and as a result effective rotational excitations and momentum conversions into the parallel to the surface are induced.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This can be rationalized by the high sticking probability of 1 at low temperatures below 320 K in Fig. 3 and the relatively small kinetic energy compared to the expected potential well depth of 270 meV for the precursor state [27]. At a higher energy of E i 180 meV, an incoming molecule collides with a more corrugated repulsive wall of the potential, and as a result effective rotational excitations and momentum conversions into the parallel to the surface are induced.…”
mentioning
confidence: 89%
“…According to the theoretical calculations [27], the geometry of the stable precursor state into the dissociative adsorption is almost parallel to the surface with CH 3 between the two dimer rows and Cl close to the lower Si of a dimer. The average orientation ( P 1 ) is closer to the surface parallel for the j212i state (hcosi 0:33) compared to the j111i state (hcosi 0:47).…”
mentioning
confidence: 99%
“…We have explored the full reaction profile corresponding to all possible dissociative adsorption modes for the dissociation of CH 3 Cl over the silicon surface. In this connection, it should be mentioned here that Romero et al 23 have identified four dissociative adsorption modes of CH 3 Cl over the silicon surface. The four dissociative adsorption modes, D2, D3, I1, and I2, identified in this present study are displayed in Figure 2.…”
Section: Articlementioning
confidence: 78%
“…They have investigated the adsorption and dissociation mechanism of CH 3 Cl on the Si (100)-2 × 1 surface using AES and LEED and also the emiempirical (PM3) method. Romero et al 23 have modified and extended the work and checked the adsorption modes employing different ab initio and density functional based methods. They have investigated the pathway of dissociation of CH 3 Cl over the silicon surface through different transition state search processes using slab geometry and also with STM images.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[92] It is quite interesting that when the |212〉 state at Ei = 120 meV was dosed on the surface, no large orientation effects were observed, as shown in Figure 11. According to theoretical calculations, [96,97] one of the possible precursors is almost parallel to the surface, with CH3 between the two dimer rows and Cl close to the lower Si of a dimer, as shown in Figure 12. The average orientation is closer to the surface parallel for the |212〉 state (〈cos γs〉 = 0.33) than the |111〉 state (〈cos γs〉 = 0.47).…”
Section: Steric Effects In Ch3cl/si(100)mentioning
confidence: 99%